1983
DOI: 10.1017/s0022172400060204
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of scarlet fever

Abstract: SUMMARYThis study attempted to find the incidence of scarlet fever in the Oxford region, including the proportion of patients from whom Streptococcus pyogenes could be isolated. General practitioners collected throat swabs from patients with suspected scarlet fever. The swabs were examined for viral and bacterial pathogens. Children admitted to hospital were used as controls. Twenty-five of 105 patients with suspected scarlet fever grew Str. pyogenes; M type 4 was the commonest type. The clinical diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Those investigators suggested that host factors, including individual and population-based immunity, must also be significant in influencing the infection potential. Among the M serotypes, M1, M2, M3, M4, M6, and M22 were detected among the isolates associated with scarlet fever (11,24,25,34). In this study, we showed that the prevalent emm types for the S. pyogenes isolates collected in central Taiwan between 1996 and 1999 were emm4 (45%), emm12 (36%), emm1 (8%), and emm22 (7%).…”
Section: Discussionmentioning
confidence: 58%
“…Those investigators suggested that host factors, including individual and population-based immunity, must also be significant in influencing the infection potential. Among the M serotypes, M1, M2, M3, M4, M6, and M22 were detected among the isolates associated with scarlet fever (11,24,25,34). In this study, we showed that the prevalent emm types for the S. pyogenes isolates collected in central Taiwan between 1996 and 1999 were emm4 (45%), emm12 (36%), emm1 (8%), and emm22 (7%).…”
Section: Discussionmentioning
confidence: 58%
“…Both emm 3 and emm 4 S. pyogenes strains have been associated with scarlet fever ( 5 ). In the Far East, emm 1 and emm 4 isolates were the leading causes of scarlet fever in the late 1990s ( 6 ), although more recently, antimicrobial drug–resistant emm 12 S. pyogenes has dominated in this region ( 7 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…M type 1 and M type 6 streptococci were isolated from single outbreaks. Perks & Mayon-White (1983), in a study of scarlet fever in the Oxford region found that 480 of the cultures were M type 4 and M type 3 was cultured from 20 % of their patients. Some 30 years ago representatives of type 4 were isolated more frequently from patients with scarlet fever than from those with uncomplicated tonsillitis (Report 1954(Report , 1957.…”
Section: Discussionmentioning
confidence: 99%